All-Optical Signal Processing - Willner, Alan E.; Khaleghi, Salman; Chitgarha, Mohammad Reza; Yilmaz, Omer Faruk (Journal of lightwave technology, 2014)
Optical signal processing brings together various fields of optics and signal processing - namely, nonlinear devices and processes, analog and digital signals, and advanced data modulation formats - to achieve high-speed signal processing functions that can potentially operate at the line rate of fiber optic communications. Information can be encoded in amplitude, phase, wavelength, polarization and spatial features of an optical wave to achieve high-capacity transmission. We revisit advances in the key enabling technologies that led to recent research in optical signal processing for digital signals that are encoded in one or more of these dimensions. Various optical nonlinearities and chromatic dispersion have been shown to enable key sub-system applications such as wavelength conversion, multicasting, multiplexing, demultiplexing, and tunable optical delays. We review recent advances in high-speed optical signal processing applications in the areas of equalization, regeneration, flexible signal generation, and optical control information (optical logic and correlation).